Analysis of the Effect of Linear and Non Linear Loads on the Effectiveness of Single Phase Transformers - Sudibya, Bambang; Irawaty, Mardiana (SENATIK STT Adisutjipto, 2018)
Lately, PLN as the state electricity company that supplmost of the electricity needs in Indonesia is being hit by a "trial" which is in a row with the burning of several Interbus Transformers (IBT) in several regions. This can be caused by the rupture of the bushing so that it triggers a short circuit and results in the burning of the transformer. However, so far the investigation of other causes has been minimal as well as the effect of the load which is primarily a nonlinear load. Electricity is a device / device that can function if it is electrified. The device / tool is used to convert electrical energy into other energy such as motion, heat, light and so on. Electricity load consists of linear load and non linear load. changes in the use of linear loads to non-linear loads, among others, from incandescent lamps to TL lamps, and many non-linear loads that are widely used such as the use of induction motors (motors used in water pumps, refrigerators, air conditioners, etc.), rectifiers, static power converter (rectifiers and or inverters), electronic ballasts cause harmonics. Harmonics are sinusoidal waves with frequencies which are round multiples of the fundamental frequency. Harmonics can affect the work function of the transformer, which causes more heating to the iron core, which causes an increase in loss. In this study, the losses will be tested if the load is linear and also if it is loaded with non-linear loads. The results showed that for small loads, the response of the two loads showed almost the same current. While for moderate loads there is a difference that has not been so large, and for large loads large currents indicated there are large differences. So that the copper losses and iron losses are greater when the load is large. Given copper losses there is a current flowing in the transformer winding and the presence of resistance in the winding (I2R1 + I2R2). so that the increase in load current will increase copper losses. So thereby increasing copper losses causes a decrease in transformer efficiency.